2019
DOI: 10.3390/catal9010042
|View full text |Cite
|
Sign up to set email alerts
|

Deoxygenation of Stearic Acid over Cobalt-Based NaX Zeolite Catalysts

Abstract: For the production of sustainable biofuels from lipid biomass it is essential to develop non-noble metal catalysts with high conversion and selectivity under inert gas atmospheres. Herein, we report a novel cobalt-based catalyst supported on zeolite NaX via ion-exchange synthesis. The resultant bifunctional cobalt-based NaX zeolite catalyst displayed high conversion of stearic acid to liquid fuels. In addition, the effect of reaction temperature and catalyst loading was studied to evaluate the order of reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 70 publications
2
6
0
Order By: Relevance
“…1 has a strong peak at 985 cm À1 with a shoulder at 890 cm À1 . This is consistent with report of Crawford et al 33 on ATR FT-IR spectra of zeolite NaX and color-indicating Zeolite NaX prepared by ion exchange with Co(II) nitrate. The peak at 985 cm À1 is due to the antisymmetric stretching vibrations of Si-O(Si) bridges in silicates.…”
Section: Resultssupporting
confidence: 93%
“…1 has a strong peak at 985 cm À1 with a shoulder at 890 cm À1 . This is consistent with report of Crawford et al 33 on ATR FT-IR spectra of zeolite NaX and color-indicating Zeolite NaX prepared by ion exchange with Co(II) nitrate. The peak at 985 cm À1 is due to the antisymmetric stretching vibrations of Si-O(Si) bridges in silicates.…”
Section: Resultssupporting
confidence: 93%
“…It has been reported that Ni-based catalysts promote the heavy hydrocarbon fractions cracking to lighter hydrocarbon fractions (Musa et al 2018). On the other hand, it has also been reported that the Co-based catalysts can enhance the C(sp 2 )-O cleavage through direct deoxygenation pathway (Bui et al 2011;Crawford et al 2019). Therefore, it is suggested that the high activity of Ni-Co/HY catalyst in both cracking and deoxygenation reactions is due to the presence of Ni and Co metals.…”
Section: Liquid Product Distributionsmentioning
confidence: 99%
“…The continuous weight loss up to 600 C was due to the oxidation of carbonaceous coke on the spent catalysts to CO 2 . 54 The feature was accompanied with the DTA proles indicating the endothermic process of carbon oxidation. For 10%Ni/Al-MCM-41 catalyst, two DTA peaks were coke such as polyaromatic carbon that required oxidation at high temperatures.…”
Section: Reusability Of 10%ni/al-mcm-41 Catalystmentioning
confidence: 96%